KARAKTERISTIK GULMA AKIBAT VARIASI DOSIS HERBISIDA OXYFLUORFEN DI PERTANAMAN KEDELAI - Ramut, Anuar; Untari, Yulis; Pani, Mario; Abdi, Zeni (Fakultas Pertanian, Universitas Janabadra, 2024)
The success factor of weed control using pre-emergent herbicides, in addition to being determined by the active ingredient, is also determined by the herbicide dose. This study aims to obtain a dose of oxyfluorfen herbicide to control weeds in soybean fields. The doses used were: 0; 400; 800; and 1.200 g a.i ha-1. The design used was a non-factorial Randomized Block Design with 3 replications. The observed variables were: percentage of weed control, percentage of weed cover and weed dry weight. The results showed that herbicide doses of 400 – 1.200 g a.i ha-1 can increase the percentage of weed control, reduce the percentage of weed cover and reduce weed dry weight.